Allelopathic Activity of Extracts from Different Brazilian Peanut (Arachis hypogaea L.) Cultivars on Lettuce (Lactuca sativa) and Weed Plants - G. S. Casimiro; E. Mansur; G. Pacheco; R. Garcia; I. C. R. Leal; N. K. Simas (The Scientific World Journal)
Peanut (Arachis hypogaea L.) is the fourth most consumed oleaginous plant in the world, producing seeds with high contents of lipids, proteins, vitamins, and carbohydrates. Biological activities of different extracts of this species have already been evaluated by many researchers, including antioxidant, antitumoral, and antibacterial. In this work, the allelopathic activity of extracts from different Brazilian peanut cultivars against lettuce (Lactuca sativa) and two weed plants (Commelina benghalensis and Ipomoea nil) was studied. Aerial parts, roots, seeds, and seed coats were used for the preparation of crude extracts. Seed extract partitioning was performed with n-hexane, dichloromethane, ethyl acetate, n-butanol, and aqueous residue. Germination and growth of hypocotyls and rootlets were evaluated after one and five days of incubation with plant extracts, respectively. Crude seed extract and its dichloromethanic partition displayed highest allelopathic activity. These results contribute for the study of new potential natural herbicides.